Not beyond the tipping point: restrained emotions and the functionality of business meals in consultancy. (3rd January 2012) - Taminiau, Yvette; Das, Enny; Berghman, Liselore; Fangman, Yuri
This paper explores the importance of business meals in shaping boundaries in informal contacts, through indepth interviews with consultants. Building on the sociology of food and embodiment, we propose three concepts as being important to understanding food mediating mechanisms: liminality, subtlety and similarity. One of the remarkable findings is the apparent contradiction that pops up in the process of breaking boundaries between consultants and clients. Consultants aim to reduce social boundaries, but not entirely, because they fear reaching a certain 'tipping point', or the point in the relationship where the informal contact is not beneficial to the professional relation.